In situ manipulation of fluorescence resonance energy transfer between quantum dots and monolayer graphene oxide by laser irradiation. Issue 3 (2nd January 2019) - He, Wenjun; Qin, Chengbing; Qiao, Zhixing; Gong, Yani; Zhang, Xiaorong; Zhang, Guofeng; Chen, Ruiyun; Gao, Yan; Xiao, Liantuan; Jia, Suotang
Abstract : Fluorescence resonance energy transfer between CdSeTe/ZnS quantum dots and monolayer graphene oxide is in situ manipulated by laser irradiation. Abstract : The unique optical properties of solution-processable colloidal semiconductor quantum dots (QDs) highlight their promising applications in the next generation of optoelectronic and biomedical technologies. In order to optimize these applications, the tunability of QDs' optical properties is always highly desired. Although the tuning during synthesis stages has been intensively investigated, the in situ alteration after device fabrication is still limited. Here we report the tuning of the optical properties of CdSeTe/ZnS QDs through an in situ manipulation of fluorescence resonance energy transfer (FRET) between QDs and monolayer graphene oxide (GO). By increasing the acceptor's absorption ability of GO through laser irradiation, the efficiency of FRET between QDs and GO has been substantially improved from 29.7% to 70.0%. The corresponding energy transfer rate is enhanced by 5.5 times. These results can be well explored by a spectral overlap between the fluorescence emission of QDs and the absorption of original or reduced GO. Our scheme, with the features of in situ manipulation, high spatial resolution and wireless steering, enables the potential functionality of such hybrid structures in optoelectronic applications.